Consideration of the logistic approach in the study subjects "Management of Intellectual Property - Timanjuk, V. N.; Timanjuk, I. V. (Problems of Engineer-Pedagogical Education, 2018)
The article considered the necessity of inclusion to the program of discipline "Intellectual Property Management" topic or section "Logistics in the field of intellectual property." This is due to the fact that the logistics as a science based on the approaches, methods, mathematical models that allow to the most rapidly and intensely to plan, monitor and manage the progress of the object, its accompanying resource flows. As a control object selected OIC which is the main through-flow of material passing along the logistics chains, ranging from the primary source - innovations (technical proposal, a patent), to a specific user. The paper invited to consider the logistics of intellectual property management system (MIS), developed and presented to the relevant terminology such basic concepts as: logistics system MIS, logistics material flow MIS, logistics MIS function, etc .; The prospects and feasibility of using logistic approach given at the list of topics and issues which is invited to consider as the base material for the new theme (section) for the study of intellectual property management.